2015
DOI: 10.1017/jfm.2015.512
|View full text |Cite
|
Sign up to set email alerts
|

On the selection of viscosity to suppress the Saffman–Taylor instability in a radially spreading annulus

Abstract: We examine the stability of a system with two radially spreading fronts in a Hele-Shaw cell in which the viscosity increases monotonically from the innermost to the outermost fluid. The critical parameters are identified as the viscosity ratio of the inner and outer fluids and the viscosity difference between the intermediate and outer fluids as a fraction of the viscosity difference between the inner and outer fluids. There is a minimum viscosity ratio of the inner and outer fluids above which, for each azimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 13 publications
4
22
0
Order By: Relevance
“…The ever increasing area available for VF and the spatially varying velocity in radial displacement affects the instability in many ways. However, the limited amount of the sample in the annulus results in features different from classical radial VF, as also observed for immiscible fluids by Beeson-Jones & Woods (2015).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The ever increasing area available for VF and the spatially varying velocity in radial displacement affects the instability in many ways. However, the limited amount of the sample in the annulus results in features different from classical radial VF, as also observed for immiscible fluids by Beeson-Jones & Woods (2015).…”
Section: Resultsmentioning
confidence: 69%
“…Recently, in context with the treatment of fluids in an oil well, Beeson-Jones & Woods (2015) considered the overall stability of the radially spreading annulus considering three fluids each having different viscosity. They reported that the results for an annulus are similar to the single interface radial flow, but depend on the viscosity difference between the inner and outer fluid.…”
Section: Introductionmentioning
confidence: 99%
“…For the case of contraction (F < 0), we shall find that the fingering instability persists and is driven primarily from the outer boundary. The annular problem is related to the 'three-layer problem' involving the radial spread of one fluid followed by another of different viscosity in a Hele-Shaw cell (Cardoso & Woods 1995;Beeson-Jones & Woods 2015). Work in this area has been much motivated by the problem of enhanced oil recovery through a porous medium.…”
Section: Introductionmentioning
confidence: 99%
“…Cardoso & Woods (1995) studied the stability of three-layer radial flows in the limiting case in which the inner interface is completely stable and looked at the break up of the middle layer into drops. Beeson-Jones & Woods (2015) analyzed general three-layer flows, and Gin & Daripa (2015) performed a linear stability analysis for an arbitrary number of fluid layers in radial geometry.…”
Section: Introductionmentioning
confidence: 99%